2019
DOI: 10.3390/su11041182
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Social Responsibility Affect the Financial Performance of the Manufacturing Sector? Evidence from an Emerging Economy

Abstract: The present study analyzed the impact of corporate social responsibility (CSR) reporting on the financial performance of Indian companies. It used secondary data from 50 manufacturing companies over the period of fiscal years 2011 to 2017. The results suggested that there exists a significant relationship between the performance of Indian companies and their CSR. The CSR not only improves the firm’s social value and reputation but also improves profitability and performance. According to the results, return on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 46 publications
7
44
0
1
Order By: Relevance
“…The closest relation was with the ROE (albeit only 13.80%), where the information of only four CSR variables was related to that ratio. Although some CSR variables positively affected financial behaviour, which agrees with several studies (Cherian et al, 2019;Chon, 2019;Isanzu & Xu, 2016) that found a positive relation with ROE, other CSR variables negatively affected it, which coincides with other studies (Sheikh, 2019) that negatively related CSR and firm leverage. To find such evidence, it may be necessary to increase the sample size.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The closest relation was with the ROE (albeit only 13.80%), where the information of only four CSR variables was related to that ratio. Although some CSR variables positively affected financial behaviour, which agrees with several studies (Cherian et al, 2019;Chon, 2019;Isanzu & Xu, 2016) that found a positive relation with ROE, other CSR variables negatively affected it, which coincides with other studies (Sheikh, 2019) that negatively related CSR and firm leverage. To find such evidence, it may be necessary to increase the sample size.…”
Section: Discussionsupporting
confidence: 91%
“…First, the study reveals that a company's sustainability transparency is well related to its size (number of employees and its assets logarithm), which coincides with other studies (Broadstock et al, ; Cherian et al, ; Kao et al, ; Liesen et al, ; Niron & Aryani, ). Some social variables are positively related to size, such as the percentage of women managers and ethnic variety, whereas the number of White people does so negatively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…that analyzed whether credit ratings, such as Standard and Poor's, take sustainability performance into account;Liang, Chang, and Shao (2018) that, while not analyzing the financial performance of banks using commonly employed variables based on revenue or assets, sought to determine whether sustainable banks are more cost efficient than their counterparts; and Xiao, Wang, van der Vaart, and van Donk (2018) that determined if country-level sustainability can be a moderating variable in the CSP-CFP relationship Hategan et al, 2018;Kim & Lee, 2018;Liang et al, 2018;Shin et al, 2016;Zhao et al, 2018;Adegbite et al, 2018;Cherian et al, 2019;Xie et al, 2018)…”
mentioning
confidence: 99%